Program Literasi Alam untuk Meningkatklan Pemahaman Lingkungan di Kalangan Pelajar Sekolah Dasar di Desa Dalu 10A Tanjung Morawa - Cut Zahara Salidia Sabrina; Revita Sari (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2025)
The 2025 Independent Community Service Program (KKN) of the University of Muhammadiyah North Sumatra was held in Dalu 10A Village, Tanjung Morawa District, Deli Serdang Regency. This activity aims to increase elementary school students' understanding and awareness of the environment through a nature literacy program. An educational approach was carried out through activities introducing organic and inorganic waste, recycling used goods, and planting seedlings in the school environment. In addition, students also carried out supporting activities such as financial management education, MSME promotion, and socialization of the importance of investment for students. The implementation results showed an increase in student awareness in maintaining school cleanliness, the emergence of environmentally conscious behavior, and active involvement of the community and school in maintaining the sustainability of the program. This KKN program successfully fostered values of social responsibility and ecological awareness among students and strengthened the synergy between students, schools, and the village community.